2014
DOI: 10.18052/www.scipress.com/ilns.13.31
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Tropical Artificial Soil by Chronic Toxicity Studies on <i>Eisenia fetida</i> against Superphosphate

Abstract: The research methodology recommended by the OECD (Organization of Economic Cooperation and Development) and ISO (International Organization for Standardization) guidelines for testing of chemicals meets the most criteria expected for ecotoxicological testing except the testing condition and the organic matter. The guidelines were initially developed by temperate countries, with testing conditions as 20 °C and the organic matter as sphagnum peat which is commonly available in those countries. But these two crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The variation of physico-chemical properties with location is not only applicable for coco peat but also for the sphagnum peat. Abbiramy et al (2012) also observed similar physico-chemical characteristics in the two peat samples. This study is also in line with their findings, except for few properties.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The variation of physico-chemical properties with location is not only applicable for coco peat but also for the sphagnum peat. Abbiramy et al (2012) also observed similar physico-chemical characteristics in the two peat samples. This study is also in line with their findings, except for few properties.…”
Section: Discussionsupporting
confidence: 66%
“…Only few studies have been conducted with various organic materials including coco peat as a replacement to sphagnum peat in artificial soil (Noguera et al, 2000;Abbiramy et al, 2012). However, acute and chronic earthworm studies with the chemicals suggested by OECD and ISO guideline are essential to validate the alternate soil so as to be included in the present OECD guideline.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of producing a composite of sewage sludge, earthworms are used as biological agents for the stabilization of organic matter. Since sewage sludge contains a large amount of organic and nutritious materials, it can be used as a suitable nutrient for feeding worms in the process of producing vermicompost (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…The use of standard artificial soil and the inclusion of alternative substrates more abundant in the study area (e.g. coir pith and coconut fiber for tropical regions) is indicated to recover results with more validity in ecotoxicological bioassays (Abbiramy et al 2012;ABNT 2014).…”
mentioning
confidence: 99%